The Drama of the American Short Story, 1800-1865 - Collins, Michael J. (Michael James), 1984- (Book collections on Project MUSE., 2016)
This book argues that to truly understand the short story form, one must look at how it was shaped by the lively, chaotic, and deeply politicized world of 19th-century transatlantic theater and performance culture. By resurrecting long-neglected theatrical influences on representative works of short fiction, Michael J. Collins demonstrates that it was the unruly culture of the stage that first energized this most significant of American art forms. Whether it was Washington Irving's first job as theater critic, Melville's politically controversial love of British drama, Alcott's thwarted dreams of stage stardom, Poe and Lippard's dramatizations of peculiarly bloodthirsty fraternity hazings, or Hawthorne's fascination with automata, theater was a key imaginative site for the major pioneers of the American short story. The book shows how perspectives from theater studies, anthropology, and performance studies can enrich readings of the short story form. Moving beyond arbitrary distinctions between performance and text, it suggests that this literature had a social life and was engaged with questions of circumatlantic and transnational culture. It suggests that the short story itself was never conceived as a nationalist literary form, but worked by mobilizing cosmopolitan connections and meanings. In so doing, the book resurrects a neglected history of American Federalism and its connections to British literary forms.